AI WAYFINDING ALGORITHM OF A MOBILE ROBOT - Norqo‘ziyev Quvonchbek Komiljon o‘g‘li; Tojiyev Alisher Hasan o‘g‘li; Sodiqov Diyorbek Sodiq o‘g‘li; Sodiqova Zilola Yahyoqul qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: Emphasizes the transformative role of AI wayfinding algorithms in mobile robot navigation. Highlights the growing importance of artificial intelligence in optimizing navigation processes across industries. Establishes the significance of efficient navigation for mobile robots across diverse applications, ranging from logistics to healthcare. Introduces the article's central focus on an artificial intelligence (AI)-based algorithm aimed at optimizing wayfinding for mobile robots.